A comprehensive test for negative frequency‐dependent selection. Issue 3 (1st May 2013) - Takahashi, Yuma; Kawata, Masakado
Abstract: Understanding the mechanisms that maintain genetic diversity within a population remains a primary challenge for evolutionary biology. Of the processes capable of maintaining variation, negative frequency‐dependent selection (NFDS), under which rare phenotypes (or alleles) enjoy a high fitness advantage, is suggested to be the most powerful. However, few experimental studies have confirmed that this process operates in nature. Although a lot of suggestive evidence has separately been provided in various polymorphic systems, these are not enough to prove the existence of NFDS in each system. Here we present a general review of NFDS and point out some problems with previous works to develop reasonable alternative research strategies for testing NFDS. In the second half of this paper, we focused on NFDS in the common bluetail damselfly, Ischnura senegalensis, that shows female‐limited genetic polymorphism. We show (1) the proximate causal mechanisms of the frequency‐dependent process, (2) frequency‐dependent inter‐morph interaction, (3) rare morph advantage and (4) morph frequency oscillations in a natural population. These results provide unequivocal empirical support for NFDS in a natural system.